Epidemiology of Trauma in Children under 18 Years of Age - Rezaei, Barreza; Tabrizi, Shahrouz; Reza Rezaei, Mohammad; Naseri, Roghaye; Reza Farnia, Mohammad (Journal of Neonatal Surgery, 2025)
Objectives: Given the increasing importance of pediatric injuries, their physical and psychological effects, and the economic burden they impose on healthcare system and regarding the substantial proportion of children and adolescents population, this study aimed to investigate the epidemiology of trauma patients, mechanisms and injuries in children under 18 years of age referred to a trauma center in west of Iran from 2015 to 2020. Method: In this retrospective study, children aged under 18 years presented to our center from 2015 to 2020 were included Data including age, gender, time of admission to the hospital, mechanism of injury, anatomical location of injury, duration of hospitalization, and interventions performed were extracted from patient data file.Statistical analysis was conducted using STATA14 software. Result: Of 42,527 cases included, 12,506 females and 30,021 males. Seventy percent of all cases were within the age range of 6 to 18 years. The duration of hospitalization was less than one day in 57.76% of cases, 1 to 5 days in 38.27%, and more than 5 days in 3.96%. The most common causes of injury were falls (18.58%) and road traffic accidents (32%). The upper extremities (50.14%), lower extremities (27.36%), and head and neck (15.32%) were the most commonly affected anatomical locations. Initial emergency interventions were provided to more than 94% of patients, while major surgical procedures, such as exploratory laparotomy and craniotomy, were performed in approximately 0.89% of cases. The incidence of trauma has been on a downward trend in recent years but has been on an upward trend again since 2019. Conclusions: Based on our study findings, the majority of cases were males. Falls and road traffic accidents are the main contributing factors to pediatric injuries. The most common anatomical location affected in children was the upper extremities. Furthermore, most patients received initial interventions, and the hospitalization duration for most cases was less than five days.